2008
DOI: 10.1902/jop.2008.070267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclosporin, Phenytoin, and Nifedipine on the Synthesis and Degradation of Gingival Collagen in Tufted Capuchin Monkeys (Cebus apella): Histochemical and MMP‐1 and −2 and Collagen I Gene Expression Analyses

Abstract: Cyclosporin, phenytoin, and nifedipine led to phased and drug-related gene expression patterns, resulting in impaired collagen metabolism, despite the lack of prominent clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Frequently, the surface epithelium has elongated rete processes. These findings are in agreement with Gurgel et al, 27 Kanno et al, 28 McKevitt and Irwni, 29 and Fujii et al 30 as they reported that CsA, PNT, and nifedipine led to phased and drug-related gene expression patterns, resulting in impaired collagen metabolism. Leask et al 31 and Chujo et al 32 found an interaction between certain fibroblasts subpopulation and collagen with PNT and its metabolite.…”
Section: Discussionsupporting
confidence: 89%
“…Frequently, the surface epithelium has elongated rete processes. These findings are in agreement with Gurgel et al, 27 Kanno et al, 28 McKevitt and Irwni, 29 and Fujii et al 30 as they reported that CsA, PNT, and nifedipine led to phased and drug-related gene expression patterns, resulting in impaired collagen metabolism. Leask et al 31 and Chujo et al 32 found an interaction between certain fibroblasts subpopulation and collagen with PNT and its metabolite.…”
Section: Discussionsupporting
confidence: 89%
“…It is estimated that about 30% to 50% of patients taking phenytoin develop significant gingival alterations (19). Microscopic analysis of Phenytoin-induced gingival overgrowth biopsies revealed a redundant tissue of apparently regular composition or with an increased amount of collagen and number of fibroblasts (20). Inhibition of synthesis or secretion of collagenase by fibroblasts is a suggested mechanism of phenytoin in wound healing (21).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological condition, the degradation of the extracellular matrix is enabled by the enzymatic activities of collagenases and matrix metalloproteinases (MMPs) coupled with a negative regulatory control by tissue inhibitor of MMPs (TIMP), which acts to inhibit the function of MMPs. It has been observed that phenytoin induced GO tissues expressed reduced levels of MMP-1, 2 and 3, while expressing elevated levels of TIMP-1 mRNA, both of which together could disrupt the matrix degradation machinery (Kato et al, 2005;Kanno et al, 2008). Besides, it may also be noted that phenytoin interferes with the cellular calcium influx (Brunet et al, 1996) and hepatic 5,10-methylenetetrahydrofolate reductase activity, both of which consequently affects the metabolism of folates.…”
Section: Discussionmentioning
confidence: 99%